Analisis Kualitas Pelayanan Publik Pada Dinas Perpustakaan dan Arsip Kabupaten Musi Rawas - Warsim, Warsim; Dani, Rahiman; Aprianty, Henny; Putra, Harry Yanza (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
This study aims to analyze the quality of public services and factors that influence services at the Library and Archives Service of Musi Rawas Regency. The method used is descriptive qualitative with a field study approach through observation, interviews, and documentation. The results of the study indicate that based on five indicators of service quality-tangible, reliability, responiveness, assurance, and empathy-services have been running quite well but still need improvement, especially in terms of physical facilities, service consistency, and attention to vulnerable groups. Factors such as compliance with procedures, communication between employees, and availability of facilities directly affect the effectiveness of services. Improvements in facilities, employee training, and ongoing evaluation are needed to realize more efficient and responive services to community needs.